2007
DOI: 10.1007/s10725-007-9212-0
|View full text |Cite
|
Sign up to set email alerts
|

The polyamine spermine induces cystocarp development in the seaweed Grateloupia (Rhodophyta)

Abstract: Polyamines such as putrescine, spermidine and spermine are ubiquitous aliphatic amines involved in reproductive events in plants and algae, and first become evident through changes in endogenous levels during reproductive development. To examine whether the differences observed in polyamines, during carposporogenesis, in the red alga Grateloupia, followed a specific pattern as is seen in other organisms, infertile axes (i.e. not showing cystocarps) were excised from the same holdfast of female fertilized indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…Further, polyamine (PAs)-aliphatic amines with relatively low molecular mass have also been studied in macroalgae with respect to their involvement in cell division (Cohen et al 1984;Garcia Jimenez et al 1998) and protection from hypo saline stress (Lee 1998;Garcia Jimenez et al 2007). Sacramento et al (2004Sacramento et al ( , 2007 and Guzman-Uriostegui et al (2002) have reported their role in maturation of reproductive structure in Grateloupia and Gracilaria cornea respectively, but their function as metal chelator to protect the seaweeds from metal induced oxidative stress has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Further, polyamine (PAs)-aliphatic amines with relatively low molecular mass have also been studied in macroalgae with respect to their involvement in cell division (Cohen et al 1984;Garcia Jimenez et al 1998) and protection from hypo saline stress (Lee 1998;Garcia Jimenez et al 2007). Sacramento et al (2004Sacramento et al ( , 2007 and Guzman-Uriostegui et al (2002) have reported their role in maturation of reproductive structure in Grateloupia and Gracilaria cornea respectively, but their function as metal chelator to protect the seaweeds from metal induced oxidative stress has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Guzmán-Urióstegui et al (2002) reported a sharp increase in endogenous levels of PAs during cystocarp development at early post-fertilization events as opposed to the PAs found in female thalli without fertilized carpogonia and mature cystocarp. Sacramento et al (2007) also reported that infertile axes from Grateloupia gametophyte thalli accumulated more PAs than those axes with cystocarps.…”
Section: Discussionmentioning
confidence: 90%
“…In marine algae, PAs have been studied with respect to their occurrence in various algal groups and their involvement in cell division (Marian et al 2000) and there is evidence for the involvement of endogenous PAs in different stages of cystocarp maturation during reproduction in Gracilaria cornea and Grateloupia sp. (Guzmán-Urióstegui et al 2002;Sacramento et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, ethylene (Figure 9.2b), a gaseous hormone involved in flowering and fruit abscission in higher plants, was recently shown to play an important role in tetrasporogenesis in red macroalgae (Order Gelidiales, Pterocladiella capillacea; García-Jim enez and Robaina, 2012). Likewise, in red macroalgae, polyamines (spermine, spermidine and putrescine; Figure 9.2c) have been shown to induce the formation of cystocarps (Order Halymeniales, Grateloupia, Sacramento, Garcia-Jimenez, and Robaina, 2007;Sacramento et al, 2007) and carpospores and their subsequent development into sporelings (Order Gracilariales Hydropuntia cornea, GuzmanUriostegui et al, 2012).…”
Section: Cytokininmentioning
confidence: 98%